Pengaruh Kinerja Keuangan Terhadap Pengungkapan Corporate Social Responsibility - Muhammad Rivandi; Annisa Annisa (Fakultas Sastra Universitas Ekasakti, 2020)
This research aims to determine the effect of leverage and profitability on disclosure of corporate social responsibility. The data is the secondary data in the form of annual reports. The population is all sectors of high profile company that is listed on the Indonesia Stock Exchange (IDX) in 2015-2019 periods and sample collection technique which are listed in by using purposive sampling, the sample is selecting samples based on certain criteria by the researcher. The samples are 42 companies. The process of hypothesis testing is done using a panel regression were processed using Eviews. Based on the test results it was found that leverage does not significantly toward the disclosure of corporate social responsibility, while profitability have a positif significant effect toward disclosure of corporate social responsibility